P-202 Nurse consultant leadership in an integrated hospice service: evaluation of impact. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Heaps, Kate; Lethem, Wendy; Dewar, Steve
Abstract : Background: More people die in hospital than wish to do so and many are from an older age group. Without action this is likely to be a growing problem. By 2030, 44% of all people dying will be over 85 years old. In 2013 a business case supported the appointment of a hospice nurse consultant with a remit to work across hospice services, particularly those provided in hospital. The aim of the post was to reduce emergency admissions, length of stay and hospital deaths. Key objectives were to: Increase use of the hospital palliative care team Ensure further integration of services Address the needs of the 'older old' Connect palliative care expertise in and out of hospital Develop strategies to meet growing demand. Methods: This evaluation draws together qualitative data and presents compelling evidence of impact against each objective. Establishing new systems and processes for referral to the hospital team and enabling rapid discharge has led to a significant reduction in deaths in non-critical hospital wards. The evaluation reviews the challenges and considers further developments. Results: Outcomes include: Referrals to the hospital team up 25% and hospital team visits up 89% A 58% increase in referrals from the hospital team to the hospice community teams A 7% decrease in deaths in non-critical hospital wards Almost 8 out of 10 patients discharge achieved within one week Increased reach to people with non-malignant disease. Conclusion: The initiative has had significant impact, far outweighing the investment required.